2018
DOI: 10.1177/1066896918763282
|View full text |Cite
|
Sign up to set email alerts
|

Intravascular Large B-Cell Lymphoma Within a Thyroid Nodule: A Diagnostic Pitfall

Abstract: Intravascular large B-cell lymphoma (IVLBCL) is a subtype of diffuse large B-cell lymphoma, where the neoplastic lymphoid proliferation resides predominantly within the lumens of blood vessels but with no or few circulating neoplastic cells in the peripheral circulation. Focal or subtle involvement in some cases can cause the diagnosis to be misinterpreted or even overlooked, delaying the initiation of appropriate treatment. Our report focuses on a 78-year-old woman with a progressively enlarging thyroid mass,… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
5
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 7 publications
(5 citation statements)
references
References 24 publications
0
5
0
Order By: Relevance
“…The nervous system and the skin are the most commonly affected areas. IVLBCL has been discovered in a growing number of tissues and organs, including the lungs, 13,14 breast, 15 uteri, 16 prostate, 17 liver, 18 kidneys, 19,20 and thyroid, 21 as awareness of the disease has increased. While this disease is uncommon in the gastrointestinal system, certain research has demonstrated that 8% (3 of 38) of IVLBCL patients manifest in the gastrointestinal system.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The nervous system and the skin are the most commonly affected areas. IVLBCL has been discovered in a growing number of tissues and organs, including the lungs, 13,14 breast, 15 uteri, 16 prostate, 17 liver, 18 kidneys, 19,20 and thyroid, 21 as awareness of the disease has increased. While this disease is uncommon in the gastrointestinal system, certain research has demonstrated that 8% (3 of 38) of IVLBCL patients manifest in the gastrointestinal system.…”
Section: Discussionmentioning
confidence: 99%
“…The most common sites are the nervous system and skin. However, with the gradual deepening of the understanding of the disease, IVLBCL has been found in an increasing number of tissues and organs, such as the lung [12,13] ,breast [14] ,uterus [15] ,prostate [16] ,liver [17] ,kidney [18,19] , and thyroid [20] . This disease is relatively rare in the gastrointestinal tract, but some studies have found that 8% (3/38) of IVLBCL case appear in the gastrointestinal tract [10] .…”
Section: Decisionmentioning
confidence: 99%
“…IVLBCL is a rare type of extranodal large B-cell lymphoma first described in 1959 by Pfleger and Tappeiner [5]. It can involve any organ of the body such as bone marrow, skin, brain, lungs, liver, spleen, thyroid, and gastrointestinal tract while lymph nodes are relatively spared [1, 2, 4, 6, 7]. IVLBCL mainly affects elderly patients, with no sex predominance.…”
Section: Discussionmentioning
confidence: 99%
“…Three-quarters of patients have stage IV disease at presentation, and 21% to 34% of cases are diagnosed at autopsy (60% of which have CNS involvement) [2]. Cases have been reported in the literature in which the diagnosis of IVLBCL was made early (at presentation) with few organs involved resulting in prompt initiation of treatment with good clinical outcome [710]. Such cases highlight the importance of the early diagnosis in conjunction with limited extent of disease in the prognosis and management of IVLBCL.…”
Section: Discussionmentioning
confidence: 99%
“…The other major pattern, more common in Asian patients, is associated with a hemophagocytic syndrome, multi-organ failure, and hepatosplenomegaly. 1,2 Historically associated with a poor prognosis, current treatment algorithms including rituximab have shown 3-year survivals of 60% to 80%. A recent study identified a high proportion of MYD88 and CD79B mutations in IVLBCL.…”
Section: Intravascular Large B-cell Lymphoma Involving Multinodular Gmentioning
confidence: 99%